Diagnosis of the inachoidid subfamily Paradasygyiinae subfam. nov (Crustacea, Decapoda, Brachyura, Majoidea) - Guinot, Danièle; van Bakel, Barry W.m. (Zootaxa, 2020)
The name for the brachyuran subfamily Dasygyiinae Holmes, 1900, recently recognised by Guinot & Van Bakel (2020) in the majoid family Inachoididae Dana, 1851, cannot be used as it is a junior synonym of Collodinae Stimpson, 1871. The present note diagnoses a new name, Paradasygyiinae subfam. nov., for the monotypic genus Paradasygyius Garth, 1958.